PENYULUHAN KESEHATAN TENTANG PENGGUNAAN ALAT PELINDUNG DIRI UNTUK MENCEGAH PENYAKIT DERMATITIS PADA NELAYAN - Reni Aprinawaty Sirait; Zul Asdar Putra Samura (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Fishermen are prone to skin diseases due to the influence of sunlight where the splash of sea air on the skin can cause itching due to its thickness by the salt pulling from the skin. sea ​​water is a cause of dermatitis with primary stimulation properties. Occupational contact dermatitis that occurs on the hands and the incidence rate for dermatitis varies from 2% to 10%. It is estimated that 5% to 7% of people with dermatitis develop chronic and 2% to 4% of whom are difficult to cure topical treatment. This method of community service consists of two stages, namely the first stage is planning the activities to be carried out, these activities are indications of needs, indications of weaknesses and solutions that will be carried out. The second stage is the implementation of which the village head has obtained permission to carry out the activity, the implementation of the activity is carried out for two days. Based on the results of community service, it was found that 80 fishermen 31 people (38.8%) had no complaints of dermatitis, 49 people (61.2%) had complaints of dermatitis. This can enable fishermen to deal with complaints of dermatitis because working as a fisherman requires that a person is often exposed directly to open weather and the irritant agent will directly damage the skin by changing the skin's pH, reacting with protein (denaturation), extracting fat from the skin layer or by reducing it. skin resistance and skin disorders are caused because the body is too long in a wet state and then it is under the sun after which it returns in a wet condition. Meanwhile, fishermen who do not experience complaints of dermatitis, fishermen who have good immunity